Structural Phase Transitions, Electronic Properties, and Hardness of RuB4under High Pressure in Comparison with FeB4and OsB4 - Kotmool, Komsilp; Tsuppayakorn-Aek, Prutthipong; Kaewmaraya, Thanayut; Pinsook, Udomsilp; Ahuja, Rajeev; Bovornratanaraks, Thiti (My University, 2020)
We have employed an evolutionary algorithm with first-principles calculations to investigate the pressure-induced structural evolution of RuB4 up to 500 GPa. The ambient phase is predicted to be a hexagonal structure (P63/mmc). The novel phases consisting of monoclinic (C2/c) and orthorhombic (Immm) structures are proposed to be the high-pressure phases at the pressure intervals of 198-388 GPa and beyond 388 GPa, respectively. The stability of the predicted phases is confirmed by both dynamic and elastic calculations. The electronic and mechanical properties of the predicted phases are evaluated and mainly discussed compared to the isoelectronic metal tetraborides, i.e., FeB4 and OsB4. In contrast to FeB4 and OsB4, all the stable phases of RuB4 are metal or semimetal, and any semiconducting phases do not emerge in the transformation pathway of RuB4. The nature of chemical bonding investigated by ELF, MPA, and pCOHP calculations reveals that the atomic configurations and the degree of covalent bonding of the predicted phases are responsible for lower hardness compared to those of FeB4 and OsB4. The results of this work provide more understanding of the family of metal tetraboride for designing metal-boride-based hard/superhard materials.